O uso do jogo Mistério no Zoo em uma sequência didática sobre vertebrados - Carla Ribeiro de Paiva Gomes (2018)
The objective of this research was to create and evaluate the effectiveness of a didactic sequence based on an investigative approach that could favor the teaching on Animal Kingdom - Vertebrates. We know that teaching about this content can be loaded with concepts and definitions, often difficult to understand by elementary students, so we created activities in which research was the main focus, seeking to value the interaction between students and construction of the knowledge from an active participation of the students, among the activities of the sequence is the Mystery Didactic Game in the Zoo ", created in 2016, with the intention of bringing the students closer to a context of investigative, playful and motivating learning. The sequence was applied in a 7th grade class and the data collection was done based on observations with records in the field notebook and audio and video recordings. The data analysis was based on a microgenetic approach of the events, following the guidelines related to Productive Disciplinary Engagement (EDP). The analyzes focused on: the description of the interactive, investigative processes and how the development of the guiding principles for the EDP were considered, which are considered to be fundamental for the good progress of activities based on this methodology. The results showed that the changes made in the game promoted a better development of the research approach and as a consequence the enrichment of the learning context. The didactic sequence obtained effective results related to the EDP covering the principles established by the authors for the promotion of participatory and productive learning.